2019
DOI: 10.1021/acsaem.8b02104
|View full text |Cite
|
Sign up to set email alerts
|

Band Alignment Strategy for Printable Triple Mesoscopic Perovskite Solar Cells with Enhanced Photovoltage

Abstract: Printable triple mesoscopic structures for organic–inorganic hybrid perovskite solar cells (PSCs) have recently obtained significant attention, and they possess a superior long-term stability in comparison to those of planar structured PSCs. In comparison with planar structures, however, triple mesoscopic structures typically show lower open-circuit voltages (V oc). Evidence suggests that nonradiative recombination governed by the mismatched energy levels between the perovskite film and the electron-transporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…As a result, the pore was well filled and the efficiency of such printable hole‐conductor‐free PSCs was boosted to a certified efficiency of 12.84% in 2014 . This method also has been reported by several other groups . In addition to 5‐AVA, other additives which can bind to substrates and perovskites at the same time such as 4‐(aminomethyl) benzoic acid hydroiodide (ABI), butylphosphonic acid 4‐ammonium (4‐ABPA) chloride, and amino‐propyltrimethoxysilane …”
Section: Modulating Morphologysupporting
confidence: 59%
“…As a result, the pore was well filled and the efficiency of such printable hole‐conductor‐free PSCs was boosted to a certified efficiency of 12.84% in 2014 . This method also has been reported by several other groups . In addition to 5‐AVA, other additives which can bind to substrates and perovskites at the same time such as 4‐(aminomethyl) benzoic acid hydroiodide (ABI), butylphosphonic acid 4‐ammonium (4‐ABPA) chloride, and amino‐propyltrimethoxysilane …”
Section: Modulating Morphologysupporting
confidence: 59%
“…Alternatively, interface modification and band alignment adjustment are also demonstrated to be efficient methods to reduce nonradiative recombination losses of interfaces. For example, a gradient bi‐layered zinc tin oxide electron transporting layer (ETL) was designed to reduce the energy loss and augments the open‐circuit voltage to be 1.02 from 0.92 V . The work function of carbon electrode was tuned by oxygen content in carbon or boron‐doping to improve hole extraction .…”
Section: Methodsmentioning
confidence: 99%
“…Combining the XPS analysis of the perovskite surface and EDS analysis of the perovskite bulk layer, it can be concluded that a gradient of Cs + ion concentration was formed in the perovskite layer from surface to bottom. The formed graded cation perovskite layer may form gradient band energy alignment to effectively reduce recombination at the perovskite/carbon interface …”
Section: Methodsmentioning
confidence: 99%
“…Thec orresponding device parameters are summarized in Table 1. [16] On the other hand, the molecular packing can be greatly affected by the substituted alkyl chains. Since control devices using doped spiro-OMeTAD also show similar hysteresis,the origin of J-V hysteresis can be ascribed to the perovskite itself including trap states,ion migration, or interface problems such as imbalance of charge transport.…”
mentioning
confidence: 99%
“…HOMO energy level in films), resulting in am ore matched interfacial band alignment with perovskite layer to increase the V OC of PVSCs. [16] On the other hand, the molecular packing can be greatly affected by the substituted alkyl chains. In our case,the longer branched alkyl chain lead to asmoother film surface and higher hole mobility.A ss uch, the proof-of…”
mentioning
confidence: 99%